The Interpretation of Prosodic Variability in the Context of Accompanying Sociophonetic Cues. Issue 1 (4th May 2017) - Warren, Paul
Production data have shown that one of the features distinguishing uptalk rises from question rises in New Zealand English (NZE) is the alignment point of the rise start, which is earlier in question utterances realized by younger speakers. Previous research has indicated that listeners are sensitive to this distinction in making a forced-choice decision as to whether an utterance is a statement or a question. NZE is also characterized by an ongoing merger of theNEAR andSQUARE diphthongs, with younger speakers more likely to realize the vowel in a word such as care with a closer starting point (as in [iɘ], overlapping with their realization of theNEAR vowel), whereas older speakers would have more open starting point (as in [eɘ]). The current study uses the mouse-tracking paradigm to provide evidence that the realization ofSQUARE with an innovative vs. a conservative variant in a word early in an utterance affects NZE listeners' sensitivity firstly to a rise as a potential signal of an uptalked statement and secondly to the early alignment of the rise as a signal of a question. This finding indicates that the interpretation of prosodic variability can depend on speaker characteristics imputed from other sociophonetic cues.